PEMANFAATAN WEBGIS UNTUK SISTEM ZONASI PENERIMAAN PESERTA DIDIK BARU SMP DAN SMA NEGERI DI KOTA BOGOR - Zaidan, Fauzan (Universitas Negeri Padang, 2024)
Since the new 2018 school year, the Ministry of Education and Culture has determined that students who will continue to the next level consider several criteria, one of which is the distance from their residence to school according to the zoning area of each school regulated by the respective local governments. Related to this, the Bogor City Government issued Guidelines for Admission of New Students in Bogor City to regulate the school zoning system. With this in mind, it is necessary to have an information system that can be accessed easily, therefore in the implementation of PPDB in Bogor City, we can utilize a website-based geographic information system (WebGIS) for school zoning. Utilization of WebGIS school zoning uses data from previous research and also attribute data obtained from the main data from the Ministry of Education. This WebGIS design uses the codeigniter and bootstrap frameworks, then writes a program to integrate the database with the program and displays the distribution of school locations and their zoning areas. The results of the design of the school zoning WebGIS are uploaded to the web hosting so that it can be accessed by the wider community via a web browser. The results of testing the black box method and the system usability scale state that WebGIS can display all existing features and work properly when accessed with laptops and mobile phones.